All‐Gas‐Phase Synthesis of Heterolayered Two‐Dimensional Nanohybrids Decorated with Metallic Nanocatalysts for Water Splitting. Issue 42 (15th September 2022) - Noh, Seonmyeong; Lee, Seungmin; Lee, Jisun; Jo, Hyemi; Lee, Haney; Kim, Minjin; Kim, Hyungwoo; Kim, Yoong Ahm; Yoon, Hyeonseok
Abstract: Herein, a sequential gas‐phase process involving air jet milling followed by chemical vapor deposition (CVD), is demonstrated to be an efficient strategy for the fabrication of heterolayered 2D nanohybrids (2DNHs) decorated with nanocatalysts. Tens of grams of the nanohybrids, which is a substantial quantity at the laboratory scale, are produced in the absence of solvents and water, and without the need for an extra purification procedure. Air jet milling enables the development of binary/ternary heterolayered structures consisting of graphene, WSe2, and/or MoS2 via the gas‐phase co‐exfoliation of their bulk counterparts. Based on the X‐ray photoelectron and Raman spectroscopy data, the heterolayers of the 2DNHs exert chemical and electronic effects on each other, while diminishing the interactions between same‐component layers. Moreover, the electrochemically active surface area increases by >190% and the charge transfer resistance decreases by >35%. CVD is performed to introduce Pt and Ru nanoparticles with diameters of a few nanometers as additional electrocatalysts into the 2DNHs. The nanocatalyst‐decorated 2DNHs show excellent performance for the production of hydrogen and oxygen gases in water‐splitting cells. Notably, the proposed all‐gas‐phase processes allow for the large‐scale production of functional 2DNHs with minimal negative environmental impact, which is crucial for the commercialization of nanomaterials. Abstract : All gas‐phase synthesis, which is more environmentally friendly, allows for the simple fabrication of heterolayered 2D nanohybrids decorated with nanocatalysts for electrocatalytic applications.